Scanning probe microscopy - Wright, Kate (NY Research Press, 2015)
Scanning Probe Microscopy (SPM) involves forming images of surfaces using a physical scanning and detection method. The key subject of this text, scanning probe microscopy is a major tool for the progress of nanotechnology with functions in a multitude of study spheres. This book comprises of unique studies on the uses of SPM methods for the classification of physical attributes of various materials at the nano level. The various topics covered in this book vary from morphology of surfaces to analyzing thin films. The diversity of topics covered in this book reflects the prominent interdisciplinary trait of the study in the sphere of scanning probe microscopy.